Symbol - Lipecka, Zofia (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Zofia Lipecka uses symbols in her artworks, treating them as the iconographic basis for the narration of the works. The following text is an author’s commentary. It contains significant references to philosophical and anthropological theories based on a deep analysis of the meanings of iconic elements. The artist’s statement is an intellectual guide through the labyrinths of her work.